Jurnal - Muhamad Dimyati; Resty Gustiawati; Ega Trisna Rahayu (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to develop a circuit training model based on volleyball techniques in extracurricular activities at the age of 13-15 years. The subjects of this study were extracurricular volleyball students at SMPN 1 Cariu. The sample in this study amounted to 10 people using random sampling. By using the questionnaire method and field trials. In conducting preliminary research, the highest score was 100 with a total of 10 items presented and expert validation with the highest score of 92 with 10 items presented. The results of this development research indicate that the development of the technique-based circuit exercise model received a good response from validators and expert practitioners, the development of the technique-based circuit training model in Kembangan into 6 posts which are used for children aged 13-15 years. This development research was tested at SMPN 1 Cariu, Bogor Regency by being witnessed by expert validators and at the same time assessing the course of the trial, and it can be concluded from the research that has been carried out on the development of a circuit training model based on volleyball game techniques in extracurricular activities at the age of 13- 15 years) is suitable for use in volleyball extracurricular exercises in junior high school (SMP).